PERENCANAAN PAKET UMRAH PLUS PADA PT MUSAFIR TOUR AND TRAVEL DI PEKANBARU - Humaira, Anisa Dewi; Sulistyani, Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This research aims to analyze the Umrah Plus package planning at PT. Musafir Tour and Travel in Pekanbaru. The main focus of this research is to identify the factors that influence tour package planning, the obstacles faced, and the efforts made to overcome them. As a company operating in the Umrah travel agency sector, PT. Musafir Tour and Travel faces the challenge of creating travel packages that are attractive, competitive and in line with consumer needs. This research uses a qualitative descriptive approach with data collection techniques in the form of interviews, observation and documentation. The research results show that the main factors influencing Umrah Plus package planning include consumer preferences for additional destinations, appropriate accommodation needs, and consumer budgets. The main obstacles faced are tight competition between travel agents and fluctuations in flight ticket prices. To overcome this obstacle, PT. Musafir Tour and Travel improves service quality and package flexibility according to consumer needs. Keywords: Package planning, Umrah plus, religious tourism, tour packages.